Materials of the round table “Phase transitions and critical phenomena: past, present, and future” (Condensed Matter Physics, 2001)
The paper contains materials of the discussion concerning phase transitions and critical phenomena which took place during the Workshop on modern problems of soft matter theory (August 27–31, 2000, Lviv, Ukraine).